2012
DOI: 10.1158/1078-0432.ccr-11-3020
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Infiltrating Immune Cells and Outcome of Merkel Cell Carcinoma: A Population-Based Study

Abstract: Results: MCPyV DNA-positive cancers contained higher numbers of CD3 Conclusions: High intratumoral T-lymphocyte counts are associated with favorable survival in MCC. Although the numbers of T cells are generally higher in MCPyV-positive than in MCPyV-negative MCC, high intratumoral T-cell counts are also associated with favorable survival in MCPyV-negative MCC.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
133
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(148 citation statements)
references
References 48 publications
(62 reference statements)
13
133
0
2
Order By: Relevance
“…Furthermore, among virus-negative tumors, a subset expressed PD-L1 and these PD-L1-positive tumors harbor a higher mutational burden as compared with PD-L1-negative tumors, which may reflect immune recognition within these tumors [89]. Notably there were also varying grades of TIL within virus-negative tumors and an increased TIL infiltration correlated with improved survival, as has been described for MCC more generally [46,48,89]. These findings indicate that among virus-negative MCCs, tumors with higher mutational burdens have increased immune recognition which may indicate that this subset may be particularly responsive to checkpoint inhibitors as has been similarly described in other cancers [92,93].…”
Section: Virus-negative Mccs and Uv-induced Neoantigensmentioning
confidence: 65%
See 3 more Smart Citations
“…Furthermore, among virus-negative tumors, a subset expressed PD-L1 and these PD-L1-positive tumors harbor a higher mutational burden as compared with PD-L1-negative tumors, which may reflect immune recognition within these tumors [89]. Notably there were also varying grades of TIL within virus-negative tumors and an increased TIL infiltration correlated with improved survival, as has been described for MCC more generally [46,48,89]. These findings indicate that among virus-negative MCCs, tumors with higher mutational burdens have increased immune recognition which may indicate that this subset may be particularly responsive to checkpoint inhibitors as has been similarly described in other cancers [92,93].…”
Section: Virus-negative Mccs and Uv-induced Neoantigensmentioning
confidence: 65%
“…reported that intratumoral FOXP3 expression was not correlated with survival in MCC, a study by Sihto et al indicated that increased FOXP3 expression was associated with improved survival [48]. Therefore, it is unclear whether Treg function is a decisive factor in immune evasion in MCC.…”
Section: T Regulatory Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The link between survival of patients with MCC and the immune system suggests that agents that promote antitumor The primary analysis population consisted of immunocompetent patients, while the overall population included both immunocompetent and immunocompromised patients. immune responses may be a beneficial treatment option for patients with MCC [20,21,33,34]. One potential mechanism used by MCC to evade the immune system is the upregulation of immune checkpoint regulators, such as PD-L1 [23].…”
Section: Discussionmentioning
confidence: 99%